Heteromericarpy of Heracleum sosnowskyi Manden. (Umbelliferae = Apiaceae) - K. G. Tkachenko (Труды по прикладной ботанике, генетике и селекции, 2020)
Background. Heracleum sosnowskyi Manden. (family Umbelliferae = Apiaceae) is included in the lists of invasive species in many regions of Russia and European countries. Mericarps (fruits conventionally called seeds) of Heracleum L. spp. are characterized by an underdeveloped embryo and a complex morphophysiological type of dormancy; two-stage stratification is needed for their germination.Methods. In the period from 2014 to 2019, fruits of H. sosnowskyi were collected near settlements in Vyborg and Gatchina Districts, Leningrad Province; collecting was carried out from August through March. Seed size and 1000 seed weight were measured. Germination experiments were performed in the laboratory (22–24°C) monthly, from the time of collection in August until May. Seeds were germinated in Petri dishes on filter paper with three replications.Results. Large seeds on marginal umbellules of the central umbel were the largest in size. Their length was from 0.6 to 1.4 cm, width from 5 to 11 mm, and 1000 seed weight from 9 to 18 g. The length of smaller fruits was from 7 to 9 mm, width from 3 to 5 mm, and 1000 seed weight from 10.5 to 11.8 g. Germination of seeds collected in late summer was protracted. Under laboratory conditions, the emergence of the first seedlings was observed after 5–7 days. For the fruits stored in the laboratory, germination was reduced. Germination rate of stratified seeds varied from 55 to 99%.Conclusion. The biometric parameters of H. sosnowskyi mericarps were slightly affected by the place of growth and the year of maturation. Under laboratory conditions, H. sosnowskyi seeds collected in August showed germination rates from 3 to 15%. In years with a warm and long autumn, part of the fruit germinated in the year of maturation and managed to reach their juvenile state. Plump mericarps remained viable for at least three years. Sosnowsky’s hogweed fruits stored under laboratory conditions lost their germination ability within a year.